2020
DOI: 10.1002/nau.24333
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of combined therapeutic effects of hydrogen sulfide donor sodium hydrogen sulfide and phosphodiesterase type‐5 inhibitor tadalafil on erectile dysfunction in a partially bladder outlet obstructed rat model

Abstract: Aims: To evaluate the impacts of hydrogen sulfide (H 2 S) donor, sodium hydrogen sulfide (NaHS), and phosphodiesterase type-5 inhibitor (PDE5i), tadalafil per se and their combination treatment on partial bladder outlet obstruction (PBOO)-induced erectile dysfunction (ED). Methods: Sprague-Dawley rats were equally divided into five groups: (a) shamoperated control; (b) PBOO; (c) PBOO-treated with NaHS (5.6 mg/kg/day, ip); (d) PBOO-treated with tadalafil (2 mg/kg/day, oral); and (e) PBOO-treated with combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
7
12
0
Order By: Relevance
“…30,36,37 Penile fibrosis in the PBOO animal model has been demonstrated in previous studies. 9,10 Supporting these data, results of our study have demonstrated a significant upregulation of TGF-β1 gene and protein expression with collagen formation in the obstructed group. NaBu, a HDAC inhibitor, attenuated fibrosis in the penile tissues of the obstructed rats by decreasing the gene and protein expression of TGF-β1 and increasing smooth muscle/collagen ratio.…”
Section: Tnf-α Levels In the Penile Tissue Of Ratssupporting
confidence: 77%
See 3 more Smart Citations
“…30,36,37 Penile fibrosis in the PBOO animal model has been demonstrated in previous studies. 9,10 Supporting these data, results of our study have demonstrated a significant upregulation of TGF-β1 gene and protein expression with collagen formation in the obstructed group. NaBu, a HDAC inhibitor, attenuated fibrosis in the penile tissues of the obstructed rats by decreasing the gene and protein expression of TGF-β1 and increasing smooth muscle/collagen ratio.…”
Section: Tnf-α Levels In the Penile Tissue Of Ratssupporting
confidence: 77%
“…As reported previously, lower nNOS protein levels in penile tissue of animals with PBOO seem to be responsible for the impaired erectile function. 6,8,10,30 In the present study, PBOO diminished relaxation responses induced by ACh (an endothelium-dependent vasodilator), which was corrected by NaBu treatment. Similarly, another HDAC inhibitor, trichostatin A increased endothelium-dependent relaxation induced by ACh in mesenteric artery from spontaneous hypertensive rats.…”
Section: Tnf-α Levels In the Penile Tissue Of Ratssupporting
confidence: 53%
See 2 more Smart Citations
“…Furthermore, a decrease in MPST expression was linked to erectile dysfunction, which is common in men who have diabetes. Rats with erectile dysfunction showed a decrease of MPST protein levels in penile tissue, which could be partially countermanded by tadalafil, a drug used to treat erectile dysfunction (Yilmaz-Oral et al 2020;Zhang et al 2016).…”
Section: Regulation Of Mpst Expression and Its Connection To Physiologymentioning
confidence: 99%